Bit Performance in Directional Oil Wells (Journal of Engineering, 2015)
This work aims to analyze and study the bit performance in directional oil wells which leads to get experience about the drilled area by monitoring bit performance and analyzing its work. This study is concerned with Rumaila Oil Field by studying directional hole of one oil well with different angles of inclination. Drilling program was used in order to compare with used parameters (WOB, RPM and FR).in those holes. The effect of the drilling hydraulic system on the bit performance was studied as well as the hydraulic calculation can be done by using Excel program. This study suggests method which is used to predict the value of penetration rate by studying different formation type to choose the best drilling parameters to drill each formation. Finally, the main aim of this research is to have the benefit from the past well drilling data to drill new wells without needing new drilling program for each well, also knowing the problems of each formation to avoid them as soon as possible through drilling the new wells, which will improve the bit performance.